2008
DOI: 10.1128/jcm.02097-07
|View full text |Cite
|
Sign up to set email alerts
|

Optochin Resistance among Streptococcus pneumoniae Strains Colonizing Healthy Children in Portugal

Abstract: Two percent of 1,973 pneumococcus strains isolated from carriers since 2001 in Portugal were found to be optochin resistant. These strains belonged to eight serotypes (and some were nontypeable), and they had diverse genetic backgrounds. Novel optochin-resistant lineages were detected over time, suggesting that there was a continuous, although sporadic, emergence of optochin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 17 publications
(19 reference statements)
6
27
0
1
Order By: Relevance
“…Opt MICs ranged from 8 to 64 g/ml for the Opt r S. pneumoniae strains (Fig. 1), which is in agreement with earlier reports on Opt resistance (2,7,11). On the other hand, the 16 Opt s subpopulations derived from heterogeneous cultures, as well as the susceptible reference strains S. pneumoniae ATCC 49619 and R6, showed MIC values of 1 to 2 g/ml, which were 4-to 64-fold lower than those obtained for their respective Opt r counterparts.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…Opt MICs ranged from 8 to 64 g/ml for the Opt r S. pneumoniae strains (Fig. 1), which is in agreement with earlier reports on Opt resistance (2,7,11). On the other hand, the 16 Opt s subpopulations derived from heterogeneous cultures, as well as the susceptible reference strains S. pneumoniae ATCC 49619 and R6, showed MIC values of 1 to 2 g/ml, which were 4-to 64-fold lower than those obtained for their respective Opt r counterparts.…”
Section: Resultssupporting
confidence: 81%
“…1). Most of the 16 different capsular types (1, 6A, 6B, 6C, 9N, 10A, 11A, 12F, 13, 14, 15C, 16F, 18C, 19A, 23A, and 23F) observed among the isolates included in the present study corresponded to types commonly found in our region (30,31), reinforcing the concept that serotype distribution among Opt r S. pneumoniae strains is mostly dependent on the epidemiological profile of each area (2,3,10,11,12). Identical serotypes were observed for the Opt r and Opt s subpopulations derived from the same culture.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations